HUBUNGAN KESEIMBANGAN DAN KOORDINASI MATA DAN KAKI TERHADAP ACCURACY SERVICE BAWAH PADA SISWA PUTRA YANG MENGIKUTI EKSTRAKURIKULER SEPAK TAKRAW SMP NEGERI 1 RANGSANG - Fikri Aulia; Slamet Slamet; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine whether there is a relationship between balance and eye and foot coordination on lower accuracy service for male students who take the football extracurricular activities at SMP Negeri 1 Rangsang. The sample of this study were male students who took the football extracurricular activity at SMP Negeri 1 Rangsang, totaling 14 people. The sampling technique was taken (total sampling) or the full sampling technique of male students who took part in the football extracurricular activity at SMP Negeri 1 Rangsang, which totaled 14 people. The results of the correlation between male students who took football takraw extracurricular activities at SMP Negeri 1 Rangsang where the first analysis was between X1 and Y where rtab was at a significant level ɑ (0.05) = rcount (0.963)> rtabel (0.553), meaning that the hypothesis was accepted and there was a strong relationship between X1 and Y. From the calculation of the second analysis X2 and Y, where r_tab is at the significant level ɑ (0.05) = means rcount 0.967)> rtabel (0.553), meaning that the hypothesis is accepted and there is a strong relationship between X2 and Y. The third analysis X1 and X2 with Y, where rtab is at the significant level ɑ (0.05) = rcount (0.972)> rtabel (0.553), it can be concluded that the relationship between X1 and X2 and Y is very strong. Key Words: Eye and Foot Balance and Coordination, Lower Accuracy Service.